Z-track technique reduces pain at the injection site, drug leakage, post-injection gluteal inflammation in Pritchard regimen for severe pre-eclamptic patients: findings from a randomized controlled trial - Babu, Jayanthy J.; Venkadalakshmi, V.; Chopra, Seema; Dhandapani, Manju (International Journal of Research in Medical Sciences, 2022)
Background: This study was conducted to compare the effect of Z track versus standard technique of intramuscular (IM) administration of magnesium sulfate (MgSO4) on level of pain at the injection site, drug leakage, post-injection gluteal inflammation in Pritchard regimen. Methods: 60 antenatal patients with pre-eclampsia (PE) admitted in the labour room were randomized for IM administration of MgSO4 by Z track technique (received all injections by Z track method) and standard technique group (received all injections by standard method). The primary outcomes were level of pain assessed by numerical rating scale, drug leakage measured by sterilized blotting paper technique and gluteal inflammation assessed by transparent grid sheet. Results: The level of pain at the injection site and drug leakage after each injection significantly increased from the 1st injection (p<0.05) to the 8th injection in both groups. Z track group experienced significantly less pain (3rd and 5th injection, p<0.05), drug leakage (p<0.05) and inflammation (both buttocks, p<0.05) compared to the standard group. Conclusions: A significant decrease in drug leakage and gluteal inflammation was observed in the Z track group. Though there was no statistically significant difference in the level of pain in both groups, the pain experienced by the Z track group was comparatively less.